Effectiveness of Gym Ball Pelvic Rocking and Breathing Relaxation Techniques in Reducing Labor Pain During the Active Phase of the First Stage at Gandrungmangu II Health Center, Cilacap - Mujiarti; Peni Cahyati; Etin Rohmatin; Santi Yuliastuti (Media Informasi, 2025)
Labor pain during the active phase of the first stage of labor is often intense and can lead to maternal exhaustion, stress, and prolonged delivery if not effectively managed. This study aimed to evaluate the effectiveness of pelvic rocking with gymball compared to breathing relaxation techniques in reducing labor pain intensity among mothers at Gandrungmangu II Health Center, Cilacap Regency. A quasi-experimental design with a two-group pretest-posttest method was employed. Forty laboring mothers were selected using purposive sampling and divided equally into two intervention groups. Pain intensity was measured using the Visual Analogue Scale (VAS) before and after the intervention. The pelvic rocking group performed exercises on a gymball, while the control group practiced breathing relaxation during contractions. The results showed a significant decrease in mean pain scores in both groups, with a more substantial reduction in the gymball group (from 8.30 to 3.10) compared to the breathing group (from 8.05 to 6.80). The p-value obtained was 0.000 (p < 0.05), indicating a statistically significant difference between the two methods. This study concludes that pelvic rocking with gymball is a more effective non-pharmacological technique for managing labor pain. It is recommended to integrate this method into standard intrapartum care in primary health facilities, supported by structured training and implementation protocols. Further research should explore its impact on labor duration, maternal satisfaction, and neonatal outcomes to enhance maternal health services.